Les enjeux de l’approvisionnement en eau au Mexique - Carlos Díaz-Delgado (Éditions en environnement VertigO, 2005)
In 2004, the population of Mexico exceeded 103 million people.  The current level of demographic growth in the country has its origin in the fast growth rate of the population, registered until the 70s of last century.  Although the growth rate has been falling since then, the population continued to increase significantly in absolute numbers. The national commission of population (CONAPO) estimates an average annual growth rate of 1.2% between 1995 and 2015, which, if attained, would be lower than the current rate of 1.8%.  Regarding the urbanization aspect, in 2000, Mexico counted 364 cities of more than 15 000 people, where more than 65% of the population of the country resided. As an example, we present the case of the Mexico Valley area (Valle de Mexico), which is located in a basin of 9 600 km2 at an average altitude of 2200 m. Most of the water used by the population of Mexico City comes from an aquifer located in the urban area, and the remainder comes from external watersheds. Bringing water to the city, aside from being an unpractical and expensive operation due to the enormous difference in altitude (> 1 km), has endangered these external watersheds (exhausting natural resources, draining rivers, etc). As another consequence, Mexico City is sinking because of the quantities of water being pumped out from beneath its ground. The city area, now one of the most populous in the world, was formerly a fertile land of lakes, and suffered from harmful human actions of water drainage and accelerated deforestation. While the city continues to grow, the problem of water supply worsens. The city is confronted with a serious risk to run out of water or to accelerate the process of draining all the surrounding areas.